Spontaneous uterine rupture complicated by bilateral pulmonary emboli: A case report - Sara Wetzler; Camila Cabrera; Peter S. Bernstein (Elsevier, 2024)
Spontaneous uterine rupture in unscarred uteri complicated by pulmonary emboli is a rare event with major maternal morbidity and mortality.This is a case of a 32-year-old woman, G1P0, at term, with no pertinent past medical/surgical history, who underwent an emergency cesarean delivery for failed induction of labor complicated by uterine rupture. Post-operatively, the patient was tachycardic and hypoxic. CT arteriogram revealed massive bilateral pulmonary emboli, and she was transferred for specialist care. An emergency pulmonary embolectomy and implantation of an extracorporeal right ventricular assist device were performed. Once the patient was clinically stable, an evaluation for thrombophilias and collagen disorders was done, and was positive for a variant of unknown significance in the ELN gene (c.205G > C).This case report highlights a potential connection between uterine ruptures, hemorrhage, and multiple, large pulmonary emboli. The authors propose a multidisciplinary discussion and evaluation to identify risk factors and biologic causes for these rare but life-threatening complications.